Evidence for the BUAS-test ability to diagnose lumbar radicular pain. Issue 1 (February 2022) - Samolsky Dekel, Boaz Gedaliahu; Sorella, Maria Cristina; Vasarri, Alessio; Melotti, Rita Maria
Background: Differential diagnosis of low back pain (LBP) is complex and a prominent issue at all health-care levels; guidance may come from patients' history cues and clinical examination signs. Human and animal studies report that diagnosis of lumbar radicular pain (LRP) may come from evaluating subjective responses of injured lumbar nerves to a strain applied at the buttock. The Buttock Applied Strain (BUAS-test) test may guide the differential diagnosis of LBP. Following an ex-adiuvantibus criterion, clinical improvement of LRP, diagnosed with the BUAS-test and congruently treated, may support this test diagnostic ability. Methods: Among 258 LRP patients, who, upon first visit (V1), tested positive on the BUAS-test (with/without positive Straight Leg Raising Test, SLRT), the effect of gabapentin prescription on painDETECT (PD) questionnaire and Brief Pain Inventory (BPI) outcomes was quantified in the follow-up visit (V2). To support BUAS-test diagnostic ability, we hypothesized that, at V2, >50% of the sample would present negative PD outcome, significant ( t -test) and ⩾2 points V2-V1 differences for each of the BPI-item's score. We used multinomial logistic regression (MLR) and χ 2 analyses to evaluate the PD-V2 outcomes' dependence upon independent variables. Results: Of the sample, 77% reported a negative PD-V2 outcome. V2-V1 differences of all BPI items were significant and >2 points. PD-V2 outcomes showed significant associations with SLRT-V1 and PD-V1, respectively, but not with gender, age group or pain site. MLR showed a significant relationship between SLRT-V1 and PD-V2 outcomes. Conclusion: Among LRP patients, diagnosed by the BUAS-test and treated with gabapentin, all prespecified endpoints were reached. These results may be considered a piece of ex-adiuvantibus evidence for the BUAS-test ability to diagnose LRP. While positive BUAS-test implies potential LRP, the co-presence with positive SLRT may imply a severer LRP condition. Further prospective research, in different settings and direct clinical measures, is needed.